Motivational Profile of Nurses - Ansell G. LAMMERT; Dagmar KALÁTOVÁ; Svetlana V. LEZHENINA; Nadezhda V. SHUVALOVA; Sergej V. SMELOV; Antonina V. KARPUNINA; Lyudmila Yu. KUPRIYANOVA; Olga B. KOLESNIKOVA (Communications of International Proceedings, 2021)
Due to the current lack of medical staff, the topic of nurses’ professional motivation is very relevant to patient care. The work of a nurse is very demanding, both mentally and physically. Therefore, healthcare personnel management should aim to support and motivate nurses to perform their highest quality work, in order to provide the highest possible level of care to patients. The aim of this survey is to examine the motivational profile of nurses by utilizing a quantitative survey, in the form of a standardized questionnaire (“Motivational profile according to Ritchie, S. and Martin, P”). The goal of this project is to develop recommendations to help constructively motivate nurses, leading to them producing the highest quality of patient care. The initial quantitative survey was conducted from 02.07.2020 to 8.07.2020, with an exploratory sample consisting of 46 respondents from the ranks of the nurses at the Department of Anesthesiology and Resuscitation at the Intensive Care Unit of “Krajskázdravotní, a.s. – Nemocnice Teplice, o.z.”(Teplice Hospital), Czech Republic. This survey confirms that as a health professional’s experience increases, a change in their work motives can be observed. Namely, one can see a transition from a predominantly physiological motivation for nursing to a predominantly social and psychological one. These results show how it is necessary for personnel management to maintain good working relationships and to maintain a good working environment, i.e. facilities and good working conditions. Some crucial concerns for a successful healthcare personnel management department to address are to solve problems or conflicts in the workplace in a timely and effective manner, to pay sufficient attention to the professional growth and development of employees, and to develop effective efficient employee evaluation and remuneration strategies.
Keywords: motivation of nurses. Motivational profile. Levels of motivation. Management in Health Care.